1973
DOI: 10.7589/0090-3558-9.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Control Whirling Disease by Continuous Drug Feeding

Abstract: Six drugs were fed continuously to susceptible trout held in known Myxosotna cerebralis contaminated water in an attempt to prevent infection. Drug efficacy was judged by comparing numbers of spores which developed in medicated and non-medicated fish. Fish after having been fed furazolidone in two tests had fewer spores than the other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…All fish, namely amprolium (Awakura & Kurahashi 1967, nitroimidazoles except metronidazole were effective Taylor et al 1973, Herwig et al 1979 Benznidazole 5…”
Section: Resultsmentioning
confidence: 99%
“…All fish, namely amprolium (Awakura & Kurahashi 1967, nitroimidazoles except metronidazole were effective Taylor et al 1973, Herwig et al 1979 Benznidazole 5…”
Section: Resultsmentioning
confidence: 99%
“…Additional eVorts have included improving habitat to reduce oligochaete populations and discovery and selective breeding of M. cerebralis-resistant trout strains for potential restocking. Control of the disease in trout farms continues to rely upon disinfection of intake waters, reducing habitat for oligochaetes by using concrete ponds, slaughter, and disinfection when the parasite is detected (El-Matbouli and HoVman, 1991;HoVman and HoVman, 1972;Taylor et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…5 In the United States, the first report of whirling disease was in 1958 in Pennsylvania, although M. cerebralis was subsequently found in trout heads from Nevada preserved in 1957. 6,15 In these cases, circumstantial evidence suggested that importations of infected frozen European rainbow trout were responsible for introduction of the disease. 6 Since that time, M. cerebralis has been found in 22 states: Alabama, California, Colorado, Connecticut, Idaho, Maryland, Massachusetts, Michigan, Montana, Nevada, New Hampshire, New Jersey, New Mexico, New York, Ohio, Oregon, Pennsylvania, Utah, Virginia, Washington, West Virginia, and Wyoming.…”
mentioning
confidence: 99%